2014
DOI: 10.1007/s10803-014-2195-6
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Perceptions of Peers with Autism Spectrum Disorder

Abstract: Little is known about peer attitudes toward college students with autism spectrum disorder (ASD). Affective, behavioral, and cognitive attitudes toward vignette characters displaying behaviors characteristic of ASD were examined among 224 four-year university students who were randomly assigned to one of three labeling conditions for the primary vignette characters: high functioning autism (HFA), typical college student, or no label. Students in the HFA label condition reported more positive behavioral and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
110
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 28 publications
17
110
2
2
Order By: Relevance
“…However, their sample was 80.4 % female. Matthews et al (2014) reported that male college students endorsed more positive affective and behavioral attitudes towards characters with autistic traits and labels in vignettes. However, men may have been more accepting of the characters in the vignettes than women because all of the characters had stereotypically male names.…”
Section: Predictors Of Baseline Knowledge and Stigma In The Us And Lementioning
confidence: 98%
See 1 more Smart Citation
“…However, their sample was 80.4 % female. Matthews et al (2014) reported that male college students endorsed more positive affective and behavioral attitudes towards characters with autistic traits and labels in vignettes. However, men may have been more accepting of the characters in the vignettes than women because all of the characters had stereotypically male names.…”
Section: Predictors Of Baseline Knowledge and Stigma In The Us And Lementioning
confidence: 98%
“…Due to mixed findings in the literature (e.g., Gardiner and Iarocci (2014); Matthews et al 2014;Nevill and White 2011), we had no hypotheses about potential associations between autistic traits and conceptions of ASD.…”
Section: Aims and Hypotheses Of The Current Studymentioning
confidence: 99%
“…This is of utmost importance, as neurotypical students are more accepting of students' idiosyncrasies when they are aware that the individual has a potential ASD diagnosis. 45 Librarians should invite panelists to present free presentations about the unique needs of students with ASD and how other students can be aware of and supportive of their college experiences. Librarians have a responsibility to provide educational opportunities for students, and this is an important topic that deserves considerable attention.…”
Section: Education For Neurotypical Studentsmentioning
confidence: 99%
“…Since then, vignettes have been used to study a range of attitudes, most notably prejudicial attitudes, including sexism (Baron, Burgess, & Kao, 1991), racism (Gilbert, 1998; Haider et al, 2011), ethnic prejudice (Hudley & Graham, 2001; Mills & Gaia, 2012), religious prejudice (Pitner, Astor, Benbenishty, Haj-Yahia, & Zeira, 2003), homophobia (St. Lawrence, Husfeldt, Kelly, Hood, & Smith, 1990), xenophobia (Caprariello, Cuddy, & Fiske, 2009), and ableism (prejudice against disabled people; Butler & Gillis, 2011; Grewal, Joy, Lewis, Swales, & Woodfield, 2002; Matthews, Ly, & Goldberg, 2015; Nevill & White, 2011; Werner, 2015). …”
Section: Vignettes As a Tool For Studying Attitudesmentioning
confidence: 99%